Uptake of medical devices approved by NICE. Issue 4 (29th August 2018) - Leng, Gillian; Williams, Sarah; Hung, Isaac; Partridge, Gemma; Sanghvi, Sonali
Abstract : Background: The UK is sometimes considered to be slow in adopting new technologies. The recent Accelerated Access Review examined adoption challenges and identified opportunities for improvements. This study aims to determine the rate of uptake of selected new medical devices approved by the National Institute for Health and Care Excellence over a 10-year period, and to consider what factors may have influenced their uptake. Methods: The selected devices were approved at least 10 years ago to ensure there was sufficient data to review uptake trends. The devices that met the selection criteria were drug-eluting coronary artery stents, the brush used in liquid-based cytology, and fluid-filled thermal balloon and microwave endometrial ablation. Data on uptake were collected from the National Audit of Percutaneous Coronary Interventions (drug-eluting stents), the national cervical screening programme (liquid-based cytology) and Hospital Episode Statistics (endometrial ablation). Results: The technologies illustrated different uptake scenarios. Liquid-based cytology showed rapid and complete uptake, probably because it was a nationally driven programme. Neither drug-eluting stents nor endometrial ablation technologies were part of a national programme, and their uptake was slower. The uptake of stents has gradually increased to 88.5% of percutaneous coronary intervention procedures in the most recent data. For both fluid-filled thermal balloon and microwave ablation, there was an increase and then decline in uptake as other technologies were developed. Conclusions: The data show excellent uptake when promoted through a nationally managed programme. Uptake was slower when left to local systems. Obtaining good, reliable data about the use of medical devices in the National Health Service (NHS) is challenging—collecting real-world data linked to electronic patient records would allow us to better track the impact of new technologies in the future. More robust implementation plans may also increase the uptake rate of cost-effective and potentially life-saving technologies into the NHS.